Systemically injected bone marrow mononuclear cells specifically home to axially vascularized tissue engineering constructs - Eweida, Ahmad; Flechtenmacher, Sophia; Sandberg, Elli; Schulte, Matthias; Schmidt, Volker-Jürgen; Kneser, Ulrich; Harhaus-Wähner, Leila (PLOS ONE, 2022)
Inducing axial vascularisation of tissue engineering constructs is a well-established method to support tissue growth in large 3-dimensional tissues. Progenitor cell chemotaxis towards axially vascularized tissues has not been well characterized. In a prospective randomized controlled study including 32 male syngeneic Lewis rats we investigated the capability of the axially vascularized constructs to attract systemically injected bone marrow mononuclear cells (BMMNCs). The underlying mechanism for cell homing was investigated focusing on the role of hypoxia and the SDF1-CXCR4-7 axis. Sixteen animals were used as donors for BMMNCs. The other animals were subjected to implantation of a tissue engineering construct in the subcutaneous groin region. These constructs were axially vascularized either via an arteriovenous loop (AVL, n = 6) or via uninterrupted flow-through vessels (non-AVL, n = 10). BMMNCs were labelled with quantum dots (Qdot® 655) and injected 12 days after surgery either via intra-arterial or intravenous routes. 2 days after cell injection, the animals were sacrificed and examined using fluorescence microscopy. The Qdot® 655 signals were detected exclusively in the liver, spleen, AVL constructs and to a minimal extent in the non-AVL constructs. A significant difference could be detected between the number of labelled cells in the AVL and non-AVL constructs with more cells detected in the AVL constructs specially in central zones (p <0.0001). The immunohistological analysis showed a significant increase in the absolute expression of HIF-1 in the AVL group in comparison to the non-AVL group. The PCR analysis confirmed a 1.4-fold increase in HIF-1 expression in AVL constructs. Although PCR analysis showed an enhanced expression of CXCR4 and CXCR7 in AVL constructs, no significant differences in SDF1 expression were detected via immunohistological or PCR analysis. At the examined time point, the AVL constructs can attract BMMNCs in a mechanism probably related to the hypoxia associated with a robust tissue formation.